Export Credit and Its Impact on The value of ‎Exports - Swamy, G Narayana; Saleem , Shaik (International Journal of Accounting and Economics Studies, 2025)
Exports play a pivotal role in India’s international trade and overall GDP growth. As export ‎credit is classified under the priority sector, scheduled commercial banks consistently extend ‎credit to the export sector, leading to a steady annual increase in outstanding export credit. ‎This study investigates the extent to which export credit contributes to the value of exports in ‎international trade. Using monthly data on export credit and export value from April 2008 to ‎March 2025, the analysis employs Autoregressive Distributed Lag (ARDL) short-run and long-run models to assess the relationship. The findings demonstrate that export credit is an ‎essential factor of export value, with a stronger influence in the long run than in the short run. ‎Additionally, export performance is positively affected by inflation and negatively impacted ‎by the exchange rate. The findings suggest that further enhancement of commercial banks’ ‎export credit under the priority sector is essential to strengthen India’s international trade ‎balance‎.
Keywords: ARDL Model; Exchange Rate; Export Credit; Export Performance; Inflation